Ucenprubart is an agonistic antibody to CD200R with the potential to treat inflammatory skin disease: preclinical development and a phase 1 clinical study - Koester, Anja; Witcher, Derrick R.; Lee, Mark; Demarest, Stephen J.; Potter, Scott; Werle, Katie; Bauer, Scott; Ruiz, Diana; Malherbe, Laurent; Poorbaugh, Josh; Glasebrook, Andrew; Preuss, Christoph; et al. (Nature communications, 2025)
CD200R is a checkpoint inhibitory receptor central to the pathogenesis of inflammatory skin disease. Here we describe the development and phase 1 clinical study (NCT03750643) of ucenprubart, a CD200R agonist antibody to downregulate immune system inflammation. Preclinical studies find ucenprubart inhibiting Fcγ receptor-induced cytokine secretion from myeloid cells in vitro and demonstrating efficacy in a mouse contact hypersensitivity model. The randomized, placebo-controlled, NCT03750643 trial assesses safety and pharmacokinetics in healthy subjects, and efficacy in atopic dermatitis patients. The primary efficacy outcome is the proportion of patients achieving Validated Investigator’s Global Assessment for Atopic Dermatitis (vIGA-AD) 0 or 1 with ≥2-point improvement from baseline at week 12. Secondary outcomes are proportions of patients achieving the primary outcome and mean changes in Eczema Area and Severity Index (EASI) and SCORing Atopic Dermatitis (SCORAD) across weeks 1 through 12, and cutoffs at week 12. Sixty-two healthy participants and 40 patients are enrolled. No serious adverse events or discontinuations due to adverse events is seen with ucenprubart. The primary endpoint is not met; however, overall improvements are observed in EASI-75 and SCORAD through 12 weeks. CD200R may be a promising therapeutic target for treating autoimmune disease, including inflammatory skin diseases. Effective treatments for atopic dermatitis (AD) are highly sought after. Here the authors develop ucenprubart (LY3454738) for treating AD and find, in a randomized, multiple arms, multicenter, placebo controlled, and dose-escalating phase 1 trial (NCT03750643) trial, ucenprubart to be safe and showing preliminary efficacy when compared with placebo at 12 weeks post treatment.